Fenologia de espécies ornitófilas e ornitocóricas em um trecho de Floreta Atlântica - Grimaldi, Mariana Castanheira (2014)
Phenology of Atlantic Forest is still ongoing issue for environmental studies. The goal of our study was to analyze and evaluate the phenology of plants pollinated and dispersed by birds on a stretch of Brazilian Atlantic Forest, in Carlos Botelho State Park (PECB) ( 24 ° 06 ' 55'' , 24 º 14' 41'' S , 47 º 47 ' 18'' and 48 º 07' 17'' W), whose climate has no distinct seasons. We hypothesized that there would be more flowers and fruits in warm period, in every community, and that would be synchrony between individuals of the same guild, regardless of the life-form. We selected five transects totaling 3000 m2, in which were collected phenological data of plant community from October 2012 to December 2013. According plants showed reproductive phenology, these were marked and monitored monthly. The plants were identified and categorized by life forms and dispersal and pollination syndromes. We calculated the diameter at breast height (DBH) and basal area by measuring the circumference at breast height (PAP) of trees, shrubs and palms with reproductive phenological event and all individuals larger than 15 cm DBH. We found 819 individuals with reproductive phonological event, which 68.6% were epiphytes and 23.2 % were small trees, shrubs and palm trees. The most observations of events in trees, small trees, shrubs and palm trees were smaller than 12 cm of DBH, which means high proportion of events in the understory (77,4 % of total of these four life form). Reproductive phenological events were correlated mainly with temperature and day length. Ornithophilous individuals accounted for 43.7 % of total records, and bird-dispersed plants represented 20.7%. The differences of ornithophilous flowers and bird-dispersed plant with ripe fruits between warm and cold periods of the occurrence were not significant for both (p=0,2856 e p=0,1606, respectively). The synchrony index of the occurrence of ornithophilous flowers and ripe fruit in bird-dispersal plants was low for both (Z=0.2684 and Z=0.2430, respectively). This low synchrony can avoid competition and promote pollination and dispersal. It is also noticed that in conservation areas where diversity is high, production of flowers and fruits occurs all year, offering resources any time.